Arachne-A web-based event viewer for MINERvA - Tagg, N (2012)
Neutrino interaction events in the detector are visually represented with a web-based tool called Arachne. Data are retrieved from a central server via AJAX, and client-side JavaScript draws images into the user's browser window using the draft HTML 5 standard. These technologies allow neutrino interactions to be viewed by anyone with a web browser, allowing for easy hand-scanning of particle interactions. Arachne has been used in to evaluate neutrino data in a prototype detector, to tune reconstruction algorithms, and for public outreach and education.